Cytokines, growth, and environment factors in bone marrow plasma of acute lymphoblastic leukemia pediatric patients - Kováč, Martin; Vášková, Martina; Petráčková, Denisa; Pelková, Vendula; Mejstříková, Ester; Kalina, Tomáš; Žaliová, Markéta; Weiser, Jaroslav; Starý, Jan; Hrušák, Ondřej (European cytokine network, 2014)
Acute lymphoblastic leukemia (ALL) cells depend on the microenvironment of the host in vivo and do not survive in in vitro culture. Conversely, the suppression of non-malignant tissues is one of the leading characteristics of the course of ALL. Both the non-malignant suppression and malignant cell survival may be partly affected by soluble factors within the bone marrow (BM) environment. Here, we aimed to identify proteins in BM plasma of children with ALL that may contribute to ALL aggressiveness and/or the microenvironment-mediated survival of ALL cells. LBMp (leukemic bone marrow plasma) at the time of ALL diagnosis was compared to control plasma of bone marrow (CBMp) or peripheral blood (CPBp) using a cytokine antibody array. The cytokine antibody array enabled simultaneous detection of 79 proteins per sample. Candidate proteins exhibiting significantly different profiles were further analyzed and confirmed by ELISA. mRNA expression of one of the candidate proteins (TIMP1) was studied using quantitative reverse transcriptase polymerase chain reaction (qRTPCR). The cytokine antibody array experiments identified 23 proteins that differed significantly (p<0.05); of these, two proteins (TIMP1 and LIF) withstood the Bonferroni correction. In contrast, little difference was observed between CBMp and CPBp. At the diagnosis of ALL, changes in the soluble microenvironment are detectable in BM plasma. These changes probably participate in the pathogenesis and/or result from the changes in the cell composition.
Keywords: leukemický inhibiční faktor; akutní lymfatická leukemie; Cytokines; dítě; cytokiny; lidé; Bone Marrow; messenger RNA; Protein Array Analysis; Leukemia Inhibitory Factor; RNA, Messenger; tkáňový inhibitor metaloproteinasy 1; kostní dřeň; Tissue Inhibitor of Metalloproteinase-1; nádorové biomarkery; čipová analýza proteinů; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Biomarkers, Tumor; Child; Cell Survival; viabilita buněk; Humans